1996
DOI: 10.2307/3579560
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Incidence of Thymic Lymphoma in AKR Mice as a Result of Chronic, Fractionated Low-Dose Total-Body X Irradiation

Abstract: We have investigated whether low-dose total-body X irradiation could suppress the development of lymphoma in AKR mice. Male mice were irradiated with 5 cGy three times a week or 15 cGy two times a week from 11 weeks of age for 40 weeks. The incidences of lymphoma were 80.5% in sham-irradiated mice, 67.5% in mice irradiated with 5 cGy three times a week and 48.6% in mice irradiated with 15 cGy twice a week. Incidence of lymphoma was significantly reduced by irradiation with 15 cGy twice a week (P = 0.006). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 12 publications
0
25
1
Order By: Relevance
“…The radiation pro-tection systems in most countries apply the LNT model even for low-dose ionizing radiation ( < 0.2 Gy). However, some reports have shown that low dose ionizing radiation can be beneficial to living organisms, which is not consistent with the predicted data by the LNT model (Luckey 1982;Liu et al 1987;Ishii et al 1996;Iyer and Lehnert 2002;. This may be explained by the fact that the LNT model is mainly based on the results of studies performed using moderate and high dose ionizing radiation.…”
Section: Introductioncontrasting
confidence: 44%
“…The radiation pro-tection systems in most countries apply the LNT model even for low-dose ionizing radiation ( < 0.2 Gy). However, some reports have shown that low dose ionizing radiation can be beneficial to living organisms, which is not consistent with the predicted data by the LNT model (Luckey 1982;Liu et al 1987;Ishii et al 1996;Iyer and Lehnert 2002;. This may be explained by the fact that the LNT model is mainly based on the results of studies performed using moderate and high dose ionizing radiation.…”
Section: Introductioncontrasting
confidence: 44%
“…Such exposures may also enhance immune reactions of the organism and attenuate harmful effects of higher doses of radiation (Liu et al 1982, 1985, Tuschl et al 1995, Safwat 2000b, Safwat et al 2003; for review see : Liu 1989, Luckey 1980, Ju et al 1995. These mechanisms may explain various epidemiological observations indicating that cancer incidence and mortality are not elevated among inhabitants of the high-versus low-background radiation areas (Ishii et al 1996, Kesavan 1997, Jagger 1998; for review see: Luckey 1999, Wei andSugahara 2000) as well as among tenants of homes with the elevated levels of radiation from 222 Rn or 60 Co (Cohen 1995, UNSCEAR 2000, Wang et al 2002, Chen et al 2004. Also, in many cohorts of nuclear workers and in the survivors of the Hiroshima and Nagasaki bombings whose absorbed doses did not exceed 0.25 Gy the incidence of leukemia and some solid tumors has been reported to be lower compared to the respective control groups (Matanoski et al 1990, Cardis et al 1995, Pierce et al 1996, McKinney et al 1998, Little et al 1999, UNSCEAR 2000, Berrington et al 2001, Katayama et al 2002 for review see: Kondo 1993, Luckey 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable additional data also indicate that, at low doses and dose rates of low Linear Energy Transfer (LET) radiation, the LNT assumption of linearity is invalid because risk is overestimated. All these other data show that low doses induce an adaptive response that reduces rather than increases risk at the molecular, cellular, and whole-animal levels (Olivieri et al, 1984;Azzam et al, 1992Azzam et al, , 1994aAzzam et al, , 1994bAzzam et al, , 1996Rigaud et al, 1993;Ishii et al, 1996;Redpath and Antoniono, 1998;Broome et al, 1999;Mitchel et al, 1999b), and does so at doses relevant to human occupational exposure. The mechanisms of these adaptive responses are the subject of intense investigation, but the discussion presented here implicates bystander effects as playing a large role in the adaptive response to radiation.…”
Section: Introductionmentioning
confidence: 99%